Laguerre polynomials as Jensen polynomials of Laguerre-Polya entire functions - Dimitrov, Dimitar Kolev [UNESP]; Cheikh, Youssef Ben (Elsevier B.V., 2009)
We prove that the only Jensen polynomials associated with an entire function in the Laguerre-Polya class that are orthogonal are the Laguerre polynomials. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Laguerre-Polya class; Jensen polynomials; Laguerre polynomial; Bessel functions; Zeros